Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex a round how we practically capture and account for complexity across a v ariety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu an d Aristotle, and with the help of a series of memorable diagrams, we a ttempt to alchemise development’s complexity into… a simple living tre e. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psyc hology, philosophy, organisational development and software engineerin g– as a way to articulate essential complexity concepts. Insights emer ging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presen ted by Prof. Chambers, Burns, Scoones and Ang in the previous seminars , to explore what complexity means in practice for development profess ionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Comp uter Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Pac kard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at th e local level, the social mobilisation processes that resulted from th e “indignados” movement in Spain and their use of ICT. At IDS, Pedro h as investigated the drivers of adaptiveness in accountability interven tions, as part of MAVC. He now coordinates the learning component of D FID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL su pports DFID country offices to experiment with the use of emerging tec hnologies to address development challenges.